A Camera-Based Type-3 Fuzzy Formation Control of Multiple Robots - Hosein-Sabzalian, M (Elsevier B.V., 2025)
The formation control (FC) for nonlinear mobile robots (MRs) during various operations is studied in this paper. An interval type-3 (T3) fuzzy logic system (FLS) based controller is introduced to enable the multiple MRs to follow the desired formation, without requiring measurement the relative pose or velocity of the follower robots. A camera is used to coordinate the motion between the leader and the followers. Additionally, the robustness of the system is analyzed in the presence of external disturbances and unknown uncertainties. T3-FLSs with novel online optimized tuning rules and adaptive mechanisms serve the dual purpose of approximating the unknown dynamics of MRs with nonholonomic constraints and implementing a fuzzy-based controller. By utilizing the Lyapunov approach, the adaptation mechanisms of the FLSs are computed, and it is proven that the closed-loop system achieves asymptotic stability. Furthermore, computer simulations are conducted to test the system s performance in terms of appropriate transient responses and robust tracking against unknown dynamics and disturbances. Simulation results demonstrate accurate tracking, and robustness under various uncertainties. The proposed method provides a computationally efficient, adaptive, and theoretically sound solution for multi-robot formation control, highlighting its potential for practical cooperative robotics applications. © 2025 The Authors